2022
DOI: 10.2478/jccm-2022-0010
|View full text |Cite
|
Sign up to set email alerts
|

Renal Manifestations and their Association with Mortality and Length of Stay in COVID-19 Patients at a Safety-net Hospital

Abstract: Background Renal involvement in COVID-19 leads to severe disease and higher mortality. We study renal parameters in COVID-19 patients and their association with mortality and length of stay in hospital. Methods A retrospective study (n=340) of confirmed COVID-19 patients with renal involvement determined by the presence of acute kidney injury. Multivariate analyses of logistic regression for mortality and linear regression fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…On the other hand, it was identified that the cohort exposed to ARI had a higher level of serum creatinine at admission compared to the non-exposed cohort (0.68% vs 0.84%), which is similar to the results obtained by Cheng et al 21 , showing that elevated creatinine levels predicted a higher probability of developing ARF during hospitalization. Furthermore, in the study by Gómez-Paz et al 22 found that higher creatinine values were related to a higher death rate in Covid-19 patients who developed ARF, which could be due to the loss of renal excretory function, giving way to the storage of nitrogenous products such as urea and creatinine. Furthermore, when there is a decrease in GFR (<50%), creatinine becomes a functional marker, its excretion depending not only on glomerular filtration but also on the renal tubules, reaching 50% as a compensation mechanism by reducing the glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, it was identified that the cohort exposed to ARI had a higher level of serum creatinine at admission compared to the non-exposed cohort (0.68% vs 0.84%), which is similar to the results obtained by Cheng et al 21 , showing that elevated creatinine levels predicted a higher probability of developing ARF during hospitalization. Furthermore, in the study by Gómez-Paz et al 22 found that higher creatinine values were related to a higher death rate in Covid-19 patients who developed ARF, which could be due to the loss of renal excretory function, giving way to the storage of nitrogenous products such as urea and creatinine. Furthermore, when there is a decrease in GFR (<50%), creatinine becomes a functional marker, its excretion depending not only on glomerular filtration but also on the renal tubules, reaching 50% as a compensation mechanism by reducing the glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in the study by Gómez-Paz et al 22 found that higher creatinine values were related to a higher death rate in Covid-19 patients who developed ARF, which could be due to the loss of renal excretory function, giving way to the storage of nitrogenous products such as urea and creatinine. Furthermore, when there is a decrease in GFR (<50%), creatinine becomes a functional marker, its excretion depending not only on glomerular filtration but also on the renal tubules, reaching 50% as a compensation mechanism by reducing the glomerular filtration rate.…”
Section: Table 01 Baseline Clinical Characteristics Of the Study Cohortsmentioning
confidence: 97%
“…Many studies have traditionally focused on laboratory parameters and respiratory factors, such as images, respiratory rate, and oxygen saturation as these have been traditionally linked with COVID-19's pulmonary nature [6,22,23]. However, recent research has identified renal parameters, including AKI and CKD, as factors that contribute to increased mortality from COVID-19 [9,[24][25][26][27]. Additionally, recent research indicates that eGFR may predict the mortality form COVID-19 [9].…”
Section: Discussionmentioning
confidence: 99%